2004
DOI: 10.1111/j.1467-8624.2004.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleepless in Chicago: Tracking the Effects of Adolescent Sleep Loss During the Middle School Years

Abstract: The influence of the sleep patterns of 2,259 students, aged 11 to 14 years, on trajectories of depressive symptoms, self-esteem, and grades was longitudinally examined using latent growth cross-domain models. Consistent with previous research, sleep decreased over time. Students who obtained less sleep in sixth grade exhibited lower initial self-esteem and grades and higher initial levels of depressive symptoms. Similarly, students who obtained less sleep over time reported heightened levels of depressive symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
313
7
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(344 citation statements)
references
References 53 publications
20
313
7
4
Order By: Relevance
“…The study here presented corroborates that of Fredriksen et al (2004) who observed emotional changes in students who slept less. It also confirms the studies of Friedman et al (1999) who compared a group of good sleepers and of poor sleepers, regarding stressful elements.…”
Section: Discussionsupporting
confidence: 81%
“…The study here presented corroborates that of Fredriksen et al (2004) who observed emotional changes in students who slept less. It also confirms the studies of Friedman et al (1999) who compared a group of good sleepers and of poor sleepers, regarding stressful elements.…”
Section: Discussionsupporting
confidence: 81%
“…Of note, the reverse association of anxiety/depression symptoms in toddlerhood predicting sleep problems in adolescence was not supported (Gregory and O'Connor 2002). Fredriksen et al (2004) also found that young adolescents who obtained less sleep over time also reported higher levels of depressive symptoms and lower self-esteem, whereas depressive symptoms and selfesteem did not predict sleep problems over time. In another study, Gregory et al (2008) found parent-reported endorsement of children/adolescents (ages 4-19) ''sleeping less than others'' to predict self-reported anxiety/depression in young adulthood (ages 18-32 years).…”
Section: Mental Healthmentioning
confidence: 92%
“…However, this study was crosssectional and evaluated only one aspect of sleep functioning. In addition, the sample was an early adolescent sample (M age = 11.9) and studies following the developmental trajectory of sleep problems suggest that difficulties with daytime sleepiness continue to increase in severity during and after the transition to high school (Fredriksen et al 2004;Shinkoda et al 2000). Accordingly, it is likely that daytime sleepiness would have an even more detrimental impact on academic functioning in an older sample of adolescents with ADHD.…”
Section: Example Psychosocial Factorsmentioning
confidence: 99%
“…The majority of studies published in the international literature about pediatric OSAS agree that this is a common SD, but considerably sub diagnosed in this population [2][3][4]20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…SD varies with age, stage of development, and ethnicity 1,2 . However, the consequences of SD seem to be universal, reflecting in the children's diurnal behavior as excessive daytime sleepiness (EDS), and mood changes 4 . The regulation of mood and modulation of emotions seem also to be affected by quantity and quality of sleep 1,3 .…”
mentioning
confidence: 99%